Alphons Diepenbrock the life, times and music of a Dutch Romantic composer. - LEO SAMAMA (TOCCATA PRESS, 2023)
The music of the Dutch composer Alphons Diepenbrock (1862-1921) is one of the glories of European late-Romantic culture, although is hardly known outside his native Netherlands. This translation makes Leo Samama's masterly study of Diepenbrock available to non-Dutch readers for the first time.